A Bifunctional Aggregation‐Induced Emission Luminogen for Monitoring and Killing of Multidrug‐Resistant Bacteria. (30th August 2018) - Li, Ying; Zhao, Zheng; Zhang, Jiangjiang; Kwok, Ryan T. K.; Xie, Sheng; Tang, Rongbing; Jia, Yuexiao; Yang, Junchuan; Wang, Le; Lam, Jacky W. Y.; Zheng, Wenfu; Jiang, Xingyu; et al.
Abstract: Multidrug‐resistant (MDR) bacteria pose serious threats to public health as there is currently a lack of effective and biocompatible drugs to kill MDR bacteria. Here, a bifunctional aggregation‐induced emission luminogen (AIEgen), triphenylethylene‐naphthalimide triazole (TriPE‐NT), is reported, which is capable of both staining and killing Gram‐positive (G+) and Gram‐negative (G−) bacteria. The intrinsic fluorescence generating ability of the TriPE unit enables TriPE‐NT to monitor the drug–bacteria interactions, meanwhile, the NT unit renders TriPE‐NT the antibacterial activity. Furthermore, TriPE‐NT can generate reactive oxygen species (ROS) under light irradiation and drastically enhance its antibacterial efficacy by photodynamic therapy against wild bacteria and clinical isolated MDR bacteria with a very low toxicity to mammalian cells. Moreover, the efficiency of TriPE‐NT staining on bacteria closely correlates with its antibacterial efficacy. As an example of application, TriPE‐NT is utilized in curing Escherichia coli‐ ( E. coli ), MDR E. coli‐, Staphylococcus epidermidis‐ ( S. epidermidis ), and MDR S. epidermidis‐ infected wounds on rats with high efficacy and high safety. Thus, TriPE‐NT can be used not only as a powerful antibiotic agent for treating MDR bacteria‐infected diseases but also as a potential fluorescent agent for monitoring the bacterial infections and further exploring the related antibacterial mechanism. Abstract : A bifunctional aggregation‐induced emission luminogen, triphenylethylene‐naphthalimide triazole (TriPE‐NT) for staining Gram‐positive or Gram‐negative bacteria and for killing the bacteria by combining both photodynamic therapy (generation of reactive oxygen species under light irradiation) and antibacterial activity of the naphthalimide triazole group is presented herein. TriPE‐NT can cure wild‐type and multidrug‐resistant bacteria‐infected wounds with high efficacy and high safety.